2019
DOI: 10.1016/j.jcmgh.2019.01.008
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-375 Suppresses the Growth and Invasion of Fibrolamellar Carcinoma

Abstract: Background & Aims Fibrolamellar carcinoma (FLC) is a rare liver cancer that primarily affects adolescents and young adults. It is characterized by a heterozygous approximately 400-kb deletion on chromosome 19 that results in a unique fusion between DnaJ heat shock protein family member B1 (DNAJB1) and the alpha catalytic subunit of protein kinase A (PRKACA). The role of microRNAs (miRNAs) in FLC remains unclear. We identified dysregulated miRNAs in FLC and investigated whether dysregulation of 1 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 61 publications
4
50
0
Order By: Relevance
“…Introducing miR-375 mimics into prFLC cells significantly suppressed YAP1 expression, reduced the expression of YAP1 target genes, and inhibited growth and migration of the cancer cells. 24 Finally, in the present study, similar responses were achieved by treating prFLC cells with verteporfin, a well-accepted pharmacologic inhibitor of YAP1. 25 YAP1 is known to maintain the proliferative and migratory capabilities of multipotent progenitors and, thus, antagonizes the terminal epithelial differentiation of such cells during development.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Introducing miR-375 mimics into prFLC cells significantly suppressed YAP1 expression, reduced the expression of YAP1 target genes, and inhibited growth and migration of the cancer cells. 24 Finally, in the present study, similar responses were achieved by treating prFLC cells with verteporfin, a well-accepted pharmacologic inhibitor of YAP1. 25 YAP1 is known to maintain the proliferative and migratory capabilities of multipotent progenitors and, thus, antagonizes the terminal epithelial differentiation of such cells during development.…”
Section: Discussionsupporting
confidence: 73%
“…These partially reprogrammed FLC cells maintain expression of the FLC signature DNAJB1-PRKACA fusion ( Figure 3D). As previously reported, such prFLC cells express YAP1 and YAP1 target genes, 24 and thus prFLC cell line and the YAP1 inhibitor drug verteporfin 25 were used to test whether inhibiting YAP1 alters tumor-associated activities (Figure 3, E and F). Compared with vehicle, verteporfin treatment significantly reduced the rate of cell growth, colony formation, and migratory capacity of prFLC cells ( Figure 3F).…”
Section: Partially Reprogrammed Flc Cell Line Identifies Yap1 As Possmentioning
confidence: 92%
“…In PLC/PRF/5 and MHCC-97L HCC cell lines, ectopic expression of miR-375 downregulated the expression level of YAP protein and CTGF mRNA, which can be transcribed by activated YAP [ 57 ]. Recently, Dinh and Jewell et al [ 58 ] found that miR-375 is the most downregulated miRNA in primary fibrolamellar carcinoma (pFLC), a rare liver cancer that primarily affects adolescents and young adults, compared with nonmalignant human livers. The loss of miR-375 was induced by the presence of the DNAJB1-PRKACA fusion gene, a hallmark of FLC, although it is yet unknown how DNAJB1-PRKACA inhibits miR-375 expression [ 58 ].…”
Section: Mirnas Interacting With the Hippo-yap/taz Signaling Pathway In Liver Cancermentioning
confidence: 99%
“…Recently, Dinh and Jewell et al [ 58 ] found that miR-375 is the most downregulated miRNA in primary fibrolamellar carcinoma (pFLC), a rare liver cancer that primarily affects adolescents and young adults, compared with nonmalignant human livers. The loss of miR-375 was induced by the presence of the DNAJB1-PRKACA fusion gene, a hallmark of FLC, although it is yet unknown how DNAJB1-PRKACA inhibits miR-375 expression [ 58 ]. As in HCC cells, the overexpression of miR-375 in FLC cells inhibited YAP and CTGF, mitigating the proliferative and migratory ability of tumor cells [ 58 ].…”
Section: Mirnas Interacting With the Hippo-yap/taz Signaling Pathway In Liver Cancermentioning
confidence: 99%
“…6,8 For instance, miRNAs from the miR-200 family repress EMT by directly targeting and downregulating ZEB1/ZEB1/ SNAIL/SLUG via miR-200-binding sites located within their 3′UTRs, resulting in enhanced E-cadherin expression and inhibition of cancer cell migration and motility. [12][13][14] On the contrary, theses EMT-TFs bind directly to the common promoter regions of the miR-200c family and cause transcriptional repression. 15 Therefore, the balance between miR-200c and EMT-TFs determines, at least in part, the status of epithelial or mesenchymal phenotype.…”
Section: Introductionmentioning
confidence: 99%